The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.47836/mjmhs.18.5.2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge, Attitude and Practice on Occupational Safety and Health Among Laboratory Workers in OSHMS Certified and Non-Certified Public Universities in Malaysia

Abstract: Introduction: The use of chemicals in teaching laboratories exposes students and laboratory staff to risk arising from hazardous chemicals. Accidents related to poor management and handling of chemicals have been reported in teaching laboratories. Good implementation of occupational safety and health (OSH) in organisation that has implemented OSH-Management System (OSH-MS) plays an important role in reducing accidents at the workplace. The aim of this study is to assess the level of knowledge, attitude and pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…These findings were in accordance with other studies conducted in Malaysia. In a prior study by Paul et al (14), it was found that there was also no correlation between knowledge level and independent variables like gender, work experience, and safety training on OSH among laboratory workers at particular public universities in Malaysia. Krishnan (15) also reported the findings of demographic factors like age and gender to have no significant influence on the application and acceptance of OSH.…”
Section: The Association Between Factors (Gender Age Working Experien...mentioning
confidence: 89%
“…These findings were in accordance with other studies conducted in Malaysia. In a prior study by Paul et al (14), it was found that there was also no correlation between knowledge level and independent variables like gender, work experience, and safety training on OSH among laboratory workers at particular public universities in Malaysia. Krishnan (15) also reported the findings of demographic factors like age and gender to have no significant influence on the application and acceptance of OSH.…”
Section: The Association Between Factors (Gender Age Working Experien...mentioning
confidence: 89%